Steroids from the blood cockle Anadara granosa - Thanh Huong, Phan Thi; Giang, Nguyen Hoang; Hong Hanh, Tran Thi; Thung, Do Cong; Cuong, Nguyen Xuan; Thanh, Nguyen Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2016)
Using various chromatographic experiments, four sterols as 5α,8α-epidioxy-24(S)-ethylcholest-6-en-3β-ol (1), (22E,24S)-5α,8α-epidioxy-24-ethyl-cholesta-6,22-dien-3β-ol (2), 7-oxocholesterol (3), and (22E)-3β-hydroxycholesta-5,22-dien-7-one (4) were isolated from the methanol extract of the blood cockle Anadara granosa. The structures of isolated compounds were elucidated by 1D and 2D-NMR experiments in comparison with reported data. This is the first report of these compounds from A. granosa.